ALASAN-ALASAN YANG MEMPENGARUHI KEPUTUSAN PEMILIHAN KARIR PADA MAHASISWA AKUNTANSI UNIVERSITAS WISNUWARDHANA MALANG - AP., S. Soedewo; Loba, Hermiyanthy T. (Magister Manajemen Universitas Wisnuwardhana, 2017)
Along with Indonesia's economic growth is expected to be better, then the accounting profession is needed in helping make it happen. This condition leads to an opportunity that is still wide open for everyone to enter the profession as an accountant, and the accountant profession as a promising career choice. Seeing the condition of the accounting profession and its role in Indonesia to date, the accounting profession has several advantages, namely the ease of entering and grabbing employment opportunities, the opportunity to improve the quality of the profession through S2 and S3 education and continuing professional education, and flexibility in determining the choice of profession public accountant, management accountant, government accountant, educator accountant). The expected objectives in this study were to find out the reasons consisting of intrinsic, income, labor market considerations, student perceptions of the firm's accounting profession, personality, type of work, and the number of job offers affecting both partially and simultaneously to career selection decisions corporate accountant. Judging from the purpose, this research uses a quantitative approach that focuses on the existence of the proof of the hypothesis created. Simultaneously in this study are independent variables consisting Intrinsic Factors, Types of Work, Student Perceptions of the company's accounting profession, Salary or Income has a significant influence on accounting student decisions in career selection as corporate accountant. Partially, independent variable consisting of Intrinsic Factor, Job Type, Student Perception about company accountant profession, Salary or Earnings have a significant influence to decision of accounting student in career selection as company accountant. While intrinsic variables have a dominant influence on student accounting decisions in career selection as a public accountant